2017
DOI: 10.1080/07370016.2017.1340764
|View full text |Cite
|
Sign up to set email alerts
|

Improving Asthma Control through Asthma Action Plans: A Quality Improvement Project at a Midwest Community Clinic

Abstract: This urban community clinic had poor asthma outcomes compared to the state of Minnesota. The standard of care supports an annual Asthma Action Plan (AAP). However, the majority of patients at this clinic had not received one. This quality improvement project aimed to improve asthma control, measured by an asthma control test of at least 20, through AAP implementation supported by all team members. The clinic's interdisciplinary champion group implemented workflow changes via practice facilitation and Plan-Do-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The use of written action plans to enable patients to adjust their medication seems to be more effective in improving health outcomes than other self-management strategies [22]; however, quality evidence is lacking [23]. A project conducted in Minnesota urban community clinics resulted in more patients having optimal asthma control (ACT ≥ 20), by increasing completion of asthma action plans and educating patients about using the plan [24]. This contrasts to the findings of a review in 2017, which concluded that asthma action plans have no effect on hospital attendance due to asthma, asthma symptom scores or adverse events [23].…”
Section: Discussionmentioning
confidence: 99%
“…The use of written action plans to enable patients to adjust their medication seems to be more effective in improving health outcomes than other self-management strategies [22]; however, quality evidence is lacking [23]. A project conducted in Minnesota urban community clinics resulted in more patients having optimal asthma control (ACT ≥ 20), by increasing completion of asthma action plans and educating patients about using the plan [24]. This contrasts to the findings of a review in 2017, which concluded that asthma action plans have no effect on hospital attendance due to asthma, asthma symptom scores or adverse events [23].…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this project was to improve participant sense of self-efficacy regarding student asthma exacerbation prevention and management through education about, and provision of, personalized student AAPs. While previous studies of AAP use have clearly demonstrated improvement in pediatric asthma management (Akhter et al, 2017;Khan et al, 2014;Lakupoch et al, 2018;Srinivas, 2015), their focus has been on use primarily in the home setting. Studies specific to school-based AAP use have generally concentrated on improving school nurse AAP initiation within schools (Egginton et al, 2013;Hanson et al, 2013;Jaramillo & Reznik, 2015;McCabe et al, 2018;Richmond et al, 2011).…”
Section: Discussionmentioning
confidence: 99%